Plasmid-Mediated Resistance to Thrombin-Induced Platelet Microbicidal Protein in Staphylococci: Role of the qacA Locus - Kupferwasser, Leon Iri (American Society for Microbiology, 1999)
Thrombin-induced platelet microbicidal protein 1 (tPMP-1) is a small, cationic peptide released from rabbit platelets following thrombin stimulation. In vitro resistance to this peptide among strains of Staphylococcus aureus correlates with the survival advantage of such strains at sites of endothelial damage in humans as well as in experimental endovascular infections. The mechanisms involved in the phenotypic resistance of S. aureus to tPMP-1 are not fully delineated. The plasmid-encoded staphylococcal gene qacA mediates multidrug resistance to multiple organic cations via a proton motive force-dependent efflux pump. We studied whether the qacA gene might also confer resistance to cationic tPMP-1. Staphylococcal plasmids encoding qacA were found to confer resistance to tPMP-1 in an otherwise susceptible parental strain. Deletions which removed the region containing the qacA gene in the S. aureus multiresistance plasmid pSK1 abolished tPMP-1 resistance. Resistance to tPMP-1 in the qacA-bearing strains was inoculum independent but peptide concentration dependent, with the level of resistance decreasing at higher peptide concentrations for a given inoculum. There was no apparent cross-resistance in qacA-bearing strains to other endogenous cationic antimicrobial peptides which are structurally distinct from tPMP-1, including human neutrophil defensin 1, protamine, or the staphylococcal lantibiotics pep5 and nisin. These data demonstrate that the staphylococcal multidrug resistance gene qacA also mediates in vitro resistance to cationic tPMP-1.